A revision of Metaleptobasis Calvert (Odonata: Coenagrionidae) with seven synonymies and the description of eighteen new species from South America - Ellenrieder, Natalia Von (Zootaxa, 2013)
Examination of over 1,400 specimens of the neotropical genus Metaleptobasis Calvert, 1907, including primary types or paratypes of 18 of the 20 currently available species names and large series of specimens including pairs in tandem and copula, allowed me to unequivocally associate older names with species, distinguish between specific and intraspecific variability, associate both sexes for each species, and recognize the existence of female polymorphism. As a result, seven names are found to be junior synonyms: Metaleptobasis mauritia Williamson, 1915 junior synonym of M. bicornis (Selys, 1877), M. manicaria Williamson, 1915 and M. fernandezi Rácenis, 1955 junior synonyms of M. diceras (Selys, 1877), M. westfalli Cumming, 1954 junior synonym of M. foreli Ris, 1915, and M. tetragena Calvert, 1947, M. weibezahni Rácenis, 1955, and M. incisula De Marmels, 1989 junior synonyms of M. brysonima Williamson, 1915. Lectotypes are designated for M. amazonica and Leptobasis diceras. Eighteen new species of Metaleptobasis are described: M. brevicauda (Holotype ♂, Peru, Huánuco Dep., Shapajilla, jungle, 11 v 1939, F. Woytkowski leg., in UMMZ); M. falcifera (Holotype ♂, Peru, Madre De Dios Dep., Pakitza, Reserved Zone, Manu National Park, T2 to R2 to T1 to base camp, 11°55’48’’S, 71°15’18’’W, 250 m, 17 ix 1989, J.A. Louton leg., in USNM); M. furcifera (Holotype ♂, Peru, Loreto Dep., Iquitos, iii 1936, G.G. Klug leg., in BMNH); M. gabrielae (Holotype ♂, Peru, Loreto Dep., Tamshiyacu-Tahuayo Reserve, forest interior (4°23’40’’S, 73°14’56’’W), 27 vii 2009, T. Faasen leg., in RMNH); M. guillermoi (Holotype ♂, Peru, Loreto Dep., Yarinacocha, temporary forest stream (8°17’S, 74°37’W, 145 m), 2 vi 1972, D.L. Pearson leg., in FSCA); M. inermis (Holotype ♂, Brazil, Pará State, Jacareacanga, vii 1969, F.R. Barbosa leg., in UMMZ); M. leniloba (Holotype ♂, Peru, Loreto Dep., Pacaya-Samiria National Reserve, Santa Luisa trail (5°15’S, 74°40’W), 10 vi 2008, C. Beatty, A. Cordero & J. Hoffmann leg., in FSCA); M. longicauda (Holotype ♂, Brazil, Mato Grosso State, C. Teles Pires, Alto Tapajos, 1–31 viii 1956, Sick leg., in MNRJ); M. orthogonia (Holotype ♂, Peru, Loreto Dep., San Juan, Río Amazonas, near Iquitos, viii 1939, J. Schunke leg., in FSCA); M. paludicola (Holotype ♂, Peru, Loreto Dep., Tamshiyacu-Tahuayo Reserve, swamp, 4°23’49’’S, 73°14’57’’W, 27 ii 2009, T. Faasen leg., in RMNH); M. panguanae (Holotype ♂, Peru, Huánuco Dep., Biological Station Panguana, E side Río Yuyapichis, 9°37’S, 74°57’W, 6–17 iv 2003, H.J. & E.-G. Burmeister leg., in ZSM); M. peltata (Holotype ♂, Peru Loreto Dep., Tamshiyacu-Tahuayo Reserve, 4°21’22’’S, 73°11’0’’W, 19 ii 2010, T. Faasen leg., in RMNH); M. prostrata (Holotype ♂, Peru, Junín Dep., Satipo, v 1945, P. Paprzycki leg., in UMMZ); M. silvicola (Holotype ♂, Peru, Madre de Dios Dep., Explorer’s Inn on Río Tambopata, 30 km SW Puerto Maldonado, main trail, 1 viii 1979, M. Perkins & P. Donahue leg., in FSCA); M. spatulata (Holotype ♂, Peru, Huánuco Dep., 10 km N of Cucharas, confluence of Huallaga and Pacay rivers, viii 1954, F. Woytkowski leg., in UMMZ); M. tridentigera (Holotype ♂, Brazil, Rondônia State, Porto Velho, Area Abunan, T11 Aleatorio, 8°46’S, 63°54’W, 86 m, 16 v 2010, Nogueira & Mendes leg., in MZUSP); M. truncata (Holotype ♂, Brazil, Pará State, Jacareacanga, xi 1969, F.R. Barbosa leg., in UMMZ); and M. turbinata (Holotype ♂, Peru, Loreto Dep., Tamshiyacu-Tahuayo Reserve, forest swamp (4°24’18’’S, 73°14’38’’W), 25 ii 2010, T. Fassen leg., in RMNH). Illustrations, keys, diagnoses, and distribution maps for all 31 currently known species are provided. Phylogenetic relationships within the genus Metaleptobasis are analyzed based on 33 adult morphological characters, including the 31 currently described species of Metaleptobasis and eleven outgroup taxa of other Coenagrionidae of the subfamily Teinobasinae. The cladistic analysis recovered Metaleptobasis as monophyletic, and as sister group of Aceratobasis Kennedy, a teinobasine genus some of the species of which possess an articulated spur on base of male cercus. Hypothesized relationships among its species are discussed.